Heat treatment of pre-hydrolyzed silane increases adhesion of phosphate monomer-based resin cement to glass ceramic - Carvalho, Rodrigo Furtado de; Cotes, Caroline [UNESP]; Kimpara, Estevão Tomomitsu [UNESP]; Leite, Fabíola Pessoa Pereira; Özcan, Mutlu (FapUNIFESP (SciELO), 2015)
This study evaluated the influence of different forms of heat treatment on a pre-hydrolyzed silane to improve the adhesion of phosphate monomer-based (MDP) resin cement to glass ceramic. Resin and feldspathic ceramic blocks (n=48, n=6 for bond test, n=2 for microscopy) were randomly divided into 6 groups and subject to surface treatments: G1: Hydrofluoric acid (HF) 9.6% for 20 s + Silane + MDP resin cement (Panavia F); G2: HF 9.6% for 20 s + Silane + Heat Treatment (oven) + Panavia F; G3: Silane + Heat Treatment (oven) + Panavia F; G4: HF 9.6% for 20 s + Silane + Heat Treatment (hot air) + Panavia F; G5: Silane + Heat Treatment (hot air) + Panavia F; G6: Silane + Panavia F. Microtensile bond strength (MTBS) test was performed using a universal testing machine (1 mm/min). After debonding, the substrate and adherent surfaces were analyzed using stereomicroscope and scanning electron microscope (SEM) to categorize the failure types. Data were analyzed statistically using two-way test ANOVA and Tukey's test (=0.05). Heat treatment of the silane containing MDP, with prior etching with HF (G2: 13.15 ± 0.89a; G4: 12.58 ± 1.03a) presented significantly higher bond strength values than the control group (G1: 9.16 ± 0.64b). The groups without prior etching (G3: 10.47 ± 0.70b; G5: 9.47 ± 0.32b) showed statistically similar bond strength values between them and the control group (G1). The silane application without prior etching and heat treatment resulted in the lowest mean bond strength (G6: 8.05 ± 0.37c). SEM analysis showed predominantly adhesive failures and EDS analysis showed common elements of spectra (Si, Na, Al, K, O, C) characterizing the microstructure of the glass-ceramic studied. Heat treatment of the pre-hydrolyzed silane containing MDP in an oven at 100 °C for 2 min or with hot air application at 50 ± 5 ºC for 1 min, was effective in increasing the bond strength values between the ceramic and resin cement containing MDP.

Este estudo avaliou o efeito de diferentes formas de tratamento térmico de um silano pré-hidrolisado na adesão de um cimento resinoso à base de monómeros fosfatados (MDP) à uma cerâmica vítrea. Blocos em resina e cerâmica feldspática (n=48, n=6 para teste de união, n=2 para microscopia) foram divididos aleatoriamente em 4 grupos e submetidos a tratamentos de superfície: G1-ácido fluorídrico (HF) 9,6% por 20 s + Silano + cimento resinoso com MDP (Panavia F) ; G2-HF 9,6% por 20 s + Silano + Tratamento Térmico (forno) + Panavia F; G3-Silano + Tratamento Térmico (forno) + Panavia F; G4-HF 9,6% por 20 s + Silano + Tratamento Térmico (ar quente) + Panavia F; G5-Silano + Tratamento Térmico (ar quente) + Panavia F; G6-Silano + Panavia F. Teste de microtração (MTBS) foi realizado utilizando máquina de ensaios universal (1 mm/min). Após o descolamento, substrato e superfícies aderentes foram analisadas utilizando estereoscópico e microscópio eletrônica de varredura (MEV) para classificação dos tipos de falha. Os dados foram analisados estatisticamente utilizando o teste ANOVA dois fatores e o teste de Tukey (α=0,05). O tratamento térmico do silano contendo MDP, com condicionamento prévio com HF (G2:13,15±0,89a e G4:12,58±1,03a) resultou em valores de resistência de união significativamente superiores aos do grupo controle (G1:9,16±0,64b). Os grupos sem condicionamento prévio (G3:10,47±0,70b e G5:9,47±0,32b), apresentaram valores de resistência de união estatisticamente semelhantes entre eles e ao controle (G1). O silano utilizado sem condicionamento prévio e tratamento térmico apresentou os menores valores de resistência de união (G6:8,05±0,37c). As análises em MEV mostraram predominância de falhas adesivas e as análises em EDS demonstraram espectros com elementos semelhantes (Si, Na, Al, K, O, C) caracterizando a microsestrutura da vitro-cerâmica estudada. O tratamento térmico do silano pré-hidrolisado contendo MDP, realizado em forno a 100 °C durante 2 min ou com ar quente a 50±5 °C durante 1 min, foi eficaz no aumento dos valores de união entre cimento resinoso contendo MDP e cerâmica.
Keywords: Cementation; Ceramics; Tensile strength; Treatment protocols